SKRINING FITOKIMIA DAN UJI TOKSISITAS EKSTRAK KASAR DAUN NIPAH (Nypa fruticans Wurmb.) - Sitti Fatimah AZ.; Erwin Erwin; Alimuddin Alimuddin (PROSIDING SEMINAR KIMIA, 2022)
Nipah (Nypa fruticans Wurmb.) is one of the plant family Arecaceae were known an used by society as a diabetes medicine, toothache, sprue and headaches. The aims of this research are to know the group of compound that containing in the extract of nipah’s leaf (Nypa fruticans Wurmb.) and determine the level of toxicity to the Artemia salina Linn. Color test and Brine Shrimp Lethality Test (BSLT) method were use for phytochemical screening and determine toxicity, respectively. The result of phytochemical screening indicate that crude extract of nipah’s leaf contains secondary metabolites of flavonoids, phenolics, saponins and steroids. The result of the toxicity test indicate that crude extract of nipah’s leaf with the LC50 20.89 ppm was very strong. Keywords: Nipah’s leaf, phytochemical and toxicity